Diversity and composition of medium and large mammals in commercial tree plantations of the Altillanura, Colombia - Lain E. Pardo; Carlos Aya-Cuero; Carlos Florez; Diana Stasiukynas (Mammalogy Notes)
The Colombian Orinoco region is one of the most important areas for agricultural development in the country. The department of Vichada, in particular, has experimented with a continuous growth of commercial tree plantations, which covered around 110589 ha by 2021. However, the potential effects of these land use changes on native mammals are not well understood. Here, we compared the diversity and composition of terrestrial mammals between tree plantations, gallery forests, and natural savannas of Puerto Carreño. We deployed 64 camera traps for eight months (5840 camera days) between August 2023 and March 2024, obtaining 1087 independent records of 23 medium and large-sized mammal species (forest: 775, plantations: 295, savanna: 17). Diversity measures indicated that gallery forest almost double folded the diversity of tree plantations, with an estimated richness of 26 and 13 species, respectively, while in the savannas we only detected four species (5 estimated). The difference in species richness between savannas and plantations was not significant. The most common species in the forest were the spotted paca (C. paca) and white-lipped peccary (T. pecari). On the other hand, white-tailed deer (O. virginianus) and crab-eating fox (C. thous) were common in savannas and plantations. Our results reaffirm the importance of riparian forests for the conservation of mammals in productive landscapes of the Altillanura and confirm that forest plantations are used by several species, two of which, were even more frequently detected in plantations than in the other covers. Our results reflect a similar composition of mammals as in non-productive landscapes, and the presence of five threatened species highlights the importance of this study area and the need for implementing conservation programs. We recommend strengthening the monitoring of natural savannas to analyze the potential effects of afforestation on this land cover.